Design and Control of Diving Mechanism for the Biomimetic Robotic Fish - Koca, Gonca Ozmen; Bingol, Mustafa Can; Bal, Cafer; Akpolat, Zuhtu Hakan; Ay, Mustafa; Korkmaz, Deniz (Springer International Publishing Ag, 2018)
This paper focuses on generating nonlinear mathematical model of the robotic fish and design a novel diving mechanism for the robotic fish prototype. For this purpose, diving behavior of a real fish is analyzed by using Kineova 8.20. The designed diving mechanism model is constructed by using moving of the sliding mass and dynamic model of robotic fish behavior is performed completely. The diving mechanism is also rearranged by adapting to the robotic fish prototype in order to obtain simple and better design performance. Hence, three dimensional motions results are obtained by using the nonlinear mathematical model and diving mechanism of the robotic fish with different diving angles.
12th International Conference on Mechatronics -- SEP 06-08, 2017 -- Brno, CZECH REPUBLIC
Keywords: Diving mechanism; Robotic fish; Pitch motion; Three dimensional motion